Improvement in electrostatic discharge robustness of a gallium‐nitride‐based flip‐chip high‐electron mobility transistor with a metal–insulator–metal capacitor structure. Issue 7 (12th March 2019) - Cheng, Nan‐Hung; Chen, Yung‐Fang; Chang, Liann‐Be; Kuei, Ping‐Yu; Ferng, Yi‐Cherng; Das, Atanu; Lin, Shu‐Liang; Lin, Ching‐Chi
Abstract : We report the improvement in the electrostatic discharge (ESD) characteristics of an AlGaN/GaN high‐electron mobility transistor (HEMT) with a metal–insulator–metal (MIM) capacitor structure on an aluminum nitride (AlN) flip‐chip (FC) submount. Compared with an HEMT without an FC, the measured results for the HEMT with an FC revealed improvements of 25% and 150% under drain‐to‐source and gate‐to‐source ESD stress, respectively. This improvement can be attributed to an additional stress‐bypassing path formed in the MIM structure on the AlN FC submount that allowed the flow of ESD current and supported the charge by using additional capacitance. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.